The role of party politics in local participation and representation: challenges and prospects in Malawi's local assemblies - Kayuni, Happy Mickson (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MPA (School of Public Management and Planning))--University of Stellenbosch, 2005.